Non increased neuron-specific enolase concentration in cerebrospinal fluid during first febrile seizures and a year follow-up in pediatric patients - ALBERTO J. DORTA-CONTRERAS; EDITH TABÍO-VALDÉS; ALINA TABÍO-VALDÉS; CARIDAD DELGADO-FERNÁNDEZ; HANSOTTO REIBER (Arquivos de Neuro-Psiquiatria)
Febrile seizures are the commonest acute neurological disorder of early childhood. Studies suggested that febrile seizures are previous acute events from a more serious neurological problem. Due to neuron-specific enolase is generally accepted as a marker for neuropathological processes in the brain, 16 pediatric patients were studied during their first seizures and a year after it. Neuron-specific enolase in cerebrospinal fluid and blood were analysed by an immune enzyme assay. Non pathological neuron-specific enolase values were obtained in both periods in the group of patients. There were no significative differences when paired series statistics test was performed with 95% of confidence. Neuron-specific enolase appears not to be a marker for febrile seizures because its concentration not be increased in cerebrospinal fluid in this group of patients.